2024
DOI: 10.1111/bph.16332
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide regulates H3 histone lactylation by interfering with p300 to alleviate aortic valve calcification

Chunli Wang,
Shunshun Wang,
Zijun Wang
et al.

Abstract: Background and PurposeOur previous studies have found that andrographolide (AGP) alleviates calcific aortic valve disease (CAVD), but the underlying mechanism is unclear. This study explores the molecular target and signal mechanisms of AGP in inhibiting CAVD.Experimental ApproachThe anti‐calcification effects of the aortic valve with AGP treatment were evaluated by alizarin red staining in vitro and ultrasound and histopathological assessment of a high‐fat (HF)‐fed ApoE−/− mouse valve calcification model. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 48 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Expression of pro-inflammatory genes induced by TNF-α was reversed by CA. The unique combination of matrix molecules, including ACAN and COL2A1 provides cartilage from damage due to load [21][22][23]. The integrity of ECM is the basis for protecting chondrocytes from stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of pro-inflammatory genes induced by TNF-α was reversed by CA. The unique combination of matrix molecules, including ACAN and COL2A1 provides cartilage from damage due to load [21][22][23]. The integrity of ECM is the basis for protecting chondrocytes from stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide (AGP) effectively reduced calcium deposition in valve interstitial cells (VICs) and improved aortic valve calcification. Wang and colleagues showed that AGP reduces calcification by disrupting H3Kla through p300 [161]. Research has demonstrated that lactylation modification plays a role in the development of atherosclerosis, making it a significant focus in atherosclerosis research, as shown in Figure 2C.…”
Section: Atherosclerosis and Lactylationmentioning
confidence: 99%